History of the treatment of persons with psychological difficulties and the abuse of their civil rights - Petrović Nikola M.; Šaćiri Bejan (Temida, 2013)
Treatment of persons with psychological difficulties varied in different historical periods, but in its essence remained similar until today. It included an inhumane relationship towards these persons, involuntary treatment through torture, and isolation from society as a kind of punishment for their diversity. It was not until the late 19th century that the relationship of society towards these individuals started to improve gradually, but in the 21st century isolation of these individuals still remained the dominant form of acceptable social solution for the “problem”, with a somewhat more humane attitude towards them and less cruel treatment. Serbia has followed the trends of treatment of the persons with psychological difficulties from the rest of Europe for centuries, but is still lagging behind the world in the introduction of new methods of treatment. Indeed the first legal solution to regulate the human rights of these people is currently in the process of implementation. The subject of this paper is the treatment of persons with psychological difficulties and the violation of their civil rights. In a subject specific context the goal of the analysis was the historical review of the treatment towards persons with psychological difficulties by doctors, other practicioners and the community in general, with reference to the current situation regarding their treatment within the psychiatric institutions, as well as the legal regulations and the protection of their civil rights.